Focus Marking And Dialect Divergence In Līkpākpáln (Konkomba) - BISILKI, Kwesi Abraham (My University, 2022)
In this paper, I discuss some salient aspects of focus marking in Likpakpaln, a Mabia (Gur), Niger-Congo language spoken mainly in the northern parts of Ghana. I compare focus marking in two dialects of Līkpākpáln, namely, Līnàjùúl and Līchábɔ́l. I treat the notion of focus from the angle of Dik (1981). Data draws from a multi-source corpora digitally recorded from stimuli-based elicitations and other natural discourse settings. Following the analysis of data, the study reveals that the use of focus particles constitutes the most significant means of focus marking in Līkpākpáln as that focus strategy is shared by both Līnàjùúl and Līchábɔ́l. Also, a common feature for both Līnàjùúl and Līchábɔ́l is that there are syntactic restrictions for the distribution of various focus particles in the sentence. On the question of divergences, I note that sentence final vowel lengthening also assumes a focus function with respect to Līnàjùúl. Also, the focus markers in Līnàjùúl (ń, ńká and a sentence final focus particle of varied phonological shapes) differ in form from the focus markers, lé and lá in Līchábɔ́l. Finally, I suggest that the focus marking differences between Līnàjùúl and Līchábɔ́l possibly stem from the fact that Līnàjùúl appears to have innovated a complex focus system vis-à-vis focus marking in the Mabia languages of Ghana. However, more thorough investigation into focus marking in other dialects of Likpakpaln and Mabia is recommended. This will help establish whether the Līnàjùúl case is an isolate system or not.
Keywords: Focus Marking; Dialect divergence; Līkpākpáln